The development of Anthropocene Awareness Scale - Donghun Kang; Moon Choi (PLoS ONE, 2025)
The political influence of the Anthropocene concept stems from its analytic potential to encompass various disciplines and capture public attention. However, there is a lack of research examining the extent to which the public has adopted the views embodied in the Anthropocene. We developed a scale to measure awareness of the Anthropocene. Based on a thorough review of Anthropocene studies, an initial set of fifteen items was generated to develop the scale. These items were then subjected to an empirical test, using a sample in South Korea (N = 1,668; aged 19 to 90). After a series of reliability and factor analyses, the Anthropocene Awareness Scale was optimized into a unidimensional scale comprising eight items (Cronbach’s alpha = 0.88). Designed to explore individual attitudes, the scale could provide quantitative researchers with an entry point into the Anthropocene discourse and facilitate empirical studies that generate evidence for environmental policies and education in the Anthropocene.